Kajian Orientasi Kewirausahaan Dengan Kinerja Pemasaran Serta Desain Strategi Pemasaran - winton, Kuswinton Winton (Akademi Sekretari Manajemen Taruna Bakti, 2024)
The decline of small businesses cannot be separated from dependence on the state, entrepreneurship is not based on the ability to manage the business and regulations are seen as unable to encourage the establishment of small businesses that are dynamic and creative. Business people who we call entrepreneurs need to cultivate a mental attitude, skills and leadership spirit in running their business. The aim of this research is the relationship between entrepreneurship and marketing performance and marketing strategy design. The method used in this research is qualitative using interviews, observation and documentation in the form of writing and images. The results of this research are the strategies used by the Idoal 1 Refillable Drinking Water Depot, namely relying on product advantages such as maintaining cleanliness, health and establishing good communication with customers as well as providing good service to consumers, carrying out online sales, renting vehicles when delivering consumer orders, maintaining the taste of drinking water so that consumers do not change, building cooperation with similar drinking water sellers, and providing maximum service such as responding quickly to consumer orders.